The Effect of Profitability and Liquidity on Company Value Empirical Study of Telecommunication Companies Listed on the IDX - Agus Setyo Utomo; Kurnia Putri Maharani (Nur Science Institute, 2023)
The phenomenon that occurred during the Covid-19 pandemic was that many telecommunications companies that went public developed amid the COVID-19 pandemic. The problem in this study is based on the uncertainty from the results of previous research (research gap) as mentioned above and the phenomenon that occurs in Indonesia with telecommunications companies, where when many other companies experience losses and even go out of business, while telecommunications companies are on the contrary. The type of research used is quantitative research. The type of data used in this research is quantitative data. The data source used in this study is a secondary data source. The population in this study are telecommunications service companies listed on the Indonesia Stock Exchange for the 2019-2021 period, totaling 19 companies. In selecting the sample to be examined, the researcher used a purposive sampling technique, namely a technique for determining the research sample with certain considerations that aim to make the data obtained later be more representative. Based on the results of the regression test, the coefficient of the profitability variable is -2.071 indicating that the profitability variable has a negative effect, and the probability significance value of 0.044 is smaller than the value determined at the 5% level, the profitability variable has a significant effect on firm value. Based on the results of the regression test, the coefficient of the liquidity variable is 3,184 indicating that the liquidity variable has a positive effect. The significance probability 0.03<0.05. shows that the liquidity variable has a significant effect on firm value. Profitability has a negative and significant effect on firm value. This means that profitability has a strong influence in relation to firm value, but an increase in profitability will make the level of firm value decrease. Liquidity has a positive and significant effect on firm value. This means that liquidity has a strong influence in relation to firm value. With increased liquidity, will increase the value of the company.